The Role of Non-State Actors in 21st Century Public Diplomacy - I Kadek Andre Nuaba (Inovasi Saintific Review, 2025)
Public diplomacy is a form of communication between actors (both government actors and non-state actors) carried out by peaceful methods and aims to form a positive image of the country abroad. Globalization has created many changes in the practice of public diplomacy, especially on media and the involvement of actors in diplomacy. Those bring openness and connectivity between actors regardless of geographical location (borderless). Thus, this article tries to analyze how the role of non-state actors in public diplomacy in the midst of globalization era. Constructivist approach of this article is to see the practice of public diplomacy not merely to achieve national interests, but how to create inter-state awareness in peaceful ways. The conclusion of this article is that non-state actors have equal power as government actors in the practice of public diplomacy, the existence of non-state actors is not to weaken the role of government actors, but to strengthen each other to achieve peace and diplomatic mission.